AL-QUR’AN MENURUT PANDANGAN ORIENTALIS (Studi Analisis ‘Teori Pengaruh’ dalam Pemikiran Orientalis) - Muzayyin, M. (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2015)
ewline"> This article tries to discuss the discourse proposed by modern western scholarship regarding to the study of polemicies about Qur’anic studies, that it is an inflence theory developed in nineteen century. The scholars used historical criticism as one of biblical method. Shortly, by using this historical criticism, they attempted to trace back the inflence of Jewish or Christian ideas toward the Qur’a>n. As a result this paper fids that when Muhammad came up with some Qur’anic doctrines, such as the history of prophethood, as well the terminology in the Qur’an; were not simply alleged or adopted from both of Jewish and Christian. This polemecies issue were popularized mainly by Abraham Geiger, then followed by Teodor Noldeke, William Muir, and John Wansbrough that will be on this article.<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;" />